The Dynamics of Manadonese Language Use in Everyday Conversation in the Digital Era - Jola Kristiani Liuw (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aims to describe the forms and dynamics of Manadonese language use in everyday conversation across two main domains: face-to-face interaction and digital communication in the modern era. This study utilizes William Labov's sociolinguistic theory, which emphasizes language variation as a systematic social phenomenon. The research method employed a descriptive qualitative approach. Data were obtained through observation, digital conversation documentation, listening and note-taking techniques, and interviews with Manadonese speakers of various age groups. The results indicate that Manadonese remains highly vital and serves as a means of intimacy, solidarity, and a marker of cultural identity, characterized by code-mixing with Indonesian and English. Shortening of language forms and linguistic creativity are widely used by the younger generation. Intergenerational variation is also evident, with the older generation maintaining a purer form of language, while the younger generation tends to adapt the language to suit the needs of digital communication. These findings demonstrate that the digital era does not weaken Manadonese, but rather expands its use and encourages the formation of new language innovations. Thus, Manadonese demonstrates strong adaptability and remains an important part of the cultural identity of the people of North Sulawesi amidst technological developments and globalization.